Pericytes: a double-edged sword in cancer therapy. (January 2015) - Meng, Mao-Bin; Zaorsky, Nicholas G; Deng, Lei; Wang, Huan-Huan; Chao, Jiang; Zhao, Lu-Jun; Yuan, Zhi-Yong; Ping, Wang
ABSTRACT : Pericytes, which envelope the vascular endothelium throughout the body, are often targeted to promote vascular normalization and restore normal function of blood vessels in cancer treatment. The goals of pericyte-targeted therapy tend to promote proper vascular normalization of the tumor. Tumor vascular normalization prevents metastasis, increases tumor oxygenation (making radiation more effective in killing tumor cells), optimizes Starling forces to increase delivery of cancer cell-directed therapies (e.g., chemotherapy or targeted agents), increases the efficacy of focal therapies (e.g., surgery or radiation), and increases recognition by the host immune system. We review how approaches in pericyte-targeted therapy aim to reach a balance between pro-angiogenic and anti-angiogenic function (i.e., by targeting platelet-derived growth factor beta receptors, vascular endothelial growth factor receptors and Tie-2) for tumor vascular normalization.